2021
DOI: 10.1071/ah21155
|View full text |Cite
|
Sign up to set email alerts
|

Implementing recovery-oriented practice in older people’s mental health services: the NSW experience

Abstract: Personal recovery is central to Australian mental health standards, but promoting recovery-oriented practice remains a wicked problem (ie complex, with definitions and appropriate interventions impacted upon by context and values), with limited evidence regarding effective implementation. This case study re-examines a statewide initiative to enhance recovery-oriented practice in older people’s mental health services in New South Wales from the perspective of complex adaptive systems. The initiative consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Supporting families and carers to help maintain a person’s identity over time is particularly important for people with dementia. Innovative methods for co-design with older people, 8 age-relevant peer work 9 and systemic changes of service orientation 10 are emerging. A statewide recovery-oriented practice project focused on older people with mental illness 11 identified strategies to support empowerment, agency and self-management as fundamental.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting families and carers to help maintain a person’s identity over time is particularly important for people with dementia. Innovative methods for co-design with older people, 8 age-relevant peer work 9 and systemic changes of service orientation 10 are emerging. A statewide recovery-oriented practice project focused on older people with mental illness 11 identified strategies to support empowerment, agency and self-management as fundamental.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting families and carers to help maintain a person's identity over time is particularly important for people with dementia. Innovative methods for co-design with older people, 8 agerelevant peer work 9 and systemic changes of service orientation 10 Mental health rehabilitation guidance specific to older people. The only relevant systematic review regarding mental health rehabilitation in older people concluded evidence was insufficient to make recommendations for an older population.…”
Section: Evidence Bases To Inform Adaptation Of Adult Rehabilitation ...mentioning
confidence: 99%
“…The concept of recovery is meant to be central for both adults under and over 65 years of age; however, previous research has indicated that healthcare workers are less likely to engage in recovery-orientated practice with OPMI. 5 Conversely, previous research has demonstrated that older people’s MHC services do not have recovery as the primary goal. 3 , 4 Koder 3 found that staff held poor attitudes towards recovery including a lack of hope for this cohort.…”
mentioning
confidence: 98%